Assessment of a simplified set of momentum closure relations for low volume fraction regimes in STAR-CCM+ and OpenFOAM. (December 2017) - Sugrue, Rosemary; Magolan, Ben; Lubchenko, Nazar; Baglietto, Emilio
Highlights: A simplified set of momentum closures – Bubbly And Moderate void Fraction (BAMF) – is proposed. BAMF model is assessed by simulation of 12 cases from the Liu and Bankoff experimental database. Portability between STAR-CCM+ and OpenFOAM CFD softwares is demonstrated. Both CFD softwares yield mean flow predictions in close agreement with experimental results. Abstract: Multiphase computational fluid dynamics (M-CFD) modeling approaches provide three-dimensional resolution of complex two-phase flow and boiling heat transfer phenomena, which makes them an invaluable tool for nuclear reactor design applications. By virtue of the Eulerian-Eulerian spatial and temporal averaging framework, additional terms manifest in the phase momentum equations that require closure through prescription of interfacial forces in the stream-wise and lateral flow directions, as well as in the near-wall region. These momentum closures are critical to M-CFD prediction of mean flow profiles, including velocity and volume fraction distributions, and yet while an overwhelming number of them has been developed, no consensus exists on how to assemble them to achieve a simplified set of closures that is numerically robust and extensible to a wide array of flow configurations; further, no consistent demonstration has been shown of the cross-code portability of these closures between CFD softwares. To address these challenges, we propose in this work a simplified set of momentum closures for stream-wise drag and lateral redistribution mechanisms—collectively referred to as the Bubbly And Moderate void Fraction (BAMF) model—and assess its performance by simulation of 12 cases from the Liu and Bankoff experimental database using STAR-CCM+ and OpenFOAM. Both CFD softwares yield mean flow predictions that are in close agreement with the experimental results, and also in close agreement with each other. These results confirm the effectiveness of the BAMF model and its portability between CFD softwares, establishing the foundation upon which future research delving into lateral redistribution and bubble-induced turbulent mechanisms will be constructed.